The Banality of Corporate Evil - Dessouki, Amina (AUC Knowledge Fountain, 2021)
This thesis critiques the notion of corporate social responsibility (CSR) through tracing the multiple dynamics between a multinational corporation and a development consultancy working on a recycling project in collaboration with the Zabaleen in Mansheyet Nasser, Egypt. The thesis looks at the ways in which actors negotiate their different positions, the harmonies and discordances that unfold through various agendas coming together, the silences produced, and the ways in which structural violence is intensified under the guise of development. The thesis contrasts the detached efforts of corporate workers and development consultants with the lives of the zabaleen, who live in a toxic, contaminated, and abandoned space. It demonstrates the ways in which the zabaleen’s life worlds and community resources get to be absorbed within wider global networks of exploitation. In a project where so-called experts design, implement, and celebrate their self-serving development plans, this thesis opens up a space for the zabaleen (the alleged beneficiaries) to narrate their own struggles and desires.